Hemodynamic performance of the balloon-expandable SAPIEN 3 valve as assessed by cardiac magnetic resonance. (1st December 2020) - Nunes Ferreira-Neto, Alfredo; Merten, Constanze; Beurich, Hans-Wilko; Zachow, Dirk; Richardt, Gert; Larose, Eric; Guimaraes, Leonardo; Pibarot, Philippe; Pelletier-Beaumont, Emilie; Rodés-Cabau, Josep; Abdel-Wahab, Mohamed
Abstract: Background: Scarce data exist on transcatheter heart valve (THV) performance evaluated by cardiac magnetic resonance (CMR) in newer generation THV patients. Furthermore, it has been suggested that echocardiographic evaluation after TAVR may inaccurately assess residual AR in some patients. This study aimed to determine the incidence and severity of aortic regurgitation (AR) assessed by CMR in patients undergoing TAVR with the SAPIEN 3 valve, and evaluate the agreement between CMR and transthoracic echocardiography (TTE) on the assessment of AR severity in such patients. Methods: This multicentric observational study included 146 SAPIEN 3 patients with TTE and CMR within the month following their procedure. According to the CMR regurgitation fraction (RF), AR was considered mild and moderate-severe if the RF was 15–<30% and ≥ 30%, respectively. TTE exams followed VARC-2 recommendations. Results: By CMR, SAPIEN 3 recipients displayed a mean RF of 5.0 ± 6.1%, and mild and moderate-severe AR rates of 3.4% and 0.7%, respectively. The agreement between CMR-TTE was modest (weighted κ = 0.2640, p<0.001), due to an overestimation of AR severity by TTE. A historical cohort of 139 SAPIEN XT patients with a post-procedure CMR, displayed a mean RF of 9.6 ± 10.7% and mild and moderate-severe AR rates of 18.7% and 3.6%, respectively ( p < .001 vs. SAPIEN 3 group). Conclusions: SAPIEN 3 recipients exhibited very low rates of residual AR by CMR, suggesting a surgical-like performance regarding AR with this newer generation THV. TTE tended to overestimate the severity of AR, particularly among mild AR patients. Highlights: SAPIEN 3 has a very low grade of residual AR as determined by CMR. Agreement of TTE and CMR on AR severity post-TAVR with the SAPIEN 3 valve is modest. TTE overestimates AR severity in close to one third of cases. CMR revealed the superiority of SAPIEN 3 versus SAPIEN XT regarding the residual AR.